Mystery calling : a qualitative application of the Lean Six Sigma approach - Latifah Abdol Latif (2010)
Service quality over the telephone is increasingly becoming a critical competitive factor to an organization’s success. A previous study (Latifah A.L et al 2009) conducted in OUM found that learners rated the following two items “university staff is easily contacted by telephone” and “toll free number for learner services center is easily reachable” as least satisfactory. This indicates that OUM’s telephone services need to be improved. To enable improvements to be made, the source of the problem needs to be identified. To achieve this, the Mystery Calling approach is used, whereby a total of 40 calls were made by a mystery caller to OUM staff. The responses from staff were rated based on a set of questions related to friendliness, professionalism, issue resolution, quality of response, and other commonly known problems generally faced by learners in telephone calling. The results are analyzed using the Lean Six Sigma 5-step method, that is, define, measure, analyse, improve and control (DMAIC) to rectify the problems encountered in telephone calling at OUM. The findings suggest that there is no standard procedure in answering telephone calls as evident by the variety of responses. In addition, it is also found that the calls were not attended to in an appropriate and timely manner. There is also a lack of knowledge on the part of the staff in terms of their inability to resolve the issues raised, not providing the relevant information and “passing the buck” to others. Finally, the attitude of the staff was found to be condescending in their dealings with learners. This paper recommends that a standard telephone response procedure be put in place and the relevant training be provided to staff. Recognising that the telephone is an ubiquitous form of communication among distance and widely distributed learners, removing their pain points in this service will immensely contribute to the enrichment of their learning experience at OUM. Finally, this study represents one of the many initiatives at OUM in attempting to improve its services to its learners in line with its learner centredness. (Authors' abstract)